Collaborative web-based teacher professional development system: a new direction for teacher professional development in Malaysia - Waheed, Hussain; Salami, Ahmed Babajide; Ali, Dahir Osman; Ahmad Dahlan, Abdul Rahman (Centre for Promoting Ideas, USA, 2011)
A collaborative web based system enables people from distributed places to work collaboratively and share information with the help of computers and network technologies. With the advance in computer technology, the use of web based instructional systems to enhance and enliven the process of teaching and learning has gained momentum in educational community. A teacher professional development system is an online learning system which provides a platform for the in-service teachers to join training, share resources and build a collaborative learning community. This paper proposes a Collaborative Web-based Teacher Professional Development System to enhance the professional development of teachers in Malaysia. It also evaluates the current situation of teacher professional development in Malaysia; describe the need for such a system in Malaysia and overview existing professional development systems.